Republic of Uzbekistan : Technical Assistance Report-External Sector Statistics Mission (October 15-26-, 2018). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
The contents of this report constitute technical advice provided by the staff of the IMF to the authorities of the Republic of Uzbekistan in response to their request for technical assistance. The main objective of the mission was to assist the Central Bank of the Republic of Uzbekistan (CBU) in improving the collection of statistical data on the balance of payments (BOP), including the adoption of an international transactions reporting system, and to assess progress in implementing the medium-term program for further development of External sector statistics. Along with the successes, the mission noted several shortages in the BOP compilation system. The transfer of the BOP compilation function from the Ministry of the Economy to the CBU, and the transition to Balance of Payments and International Investment Position Manual, sixth edition standards, have led to a data gap between the BOP compiled by two institutions. It is recommended to update the methodology for calculating the currency and deposits of households component per the mission's recommendations, considering all possible inflows and outflows of foreign currency in cash by individuals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet